Kalakuan Bubuhan Cucu Kai: Dua Sisi Kehidupan Remaja Pemain Judi Slot Dalam Bermasyarakat - Ahmad Riyadi; Arif Rahman Hakim (Huma: Jurnal Sosiologi, 2023)
In Telaga Silaba Village there is a group of teenagers who often play slot gambling so that they are seen as a group with negative behavior, but they are also seen as a group with positive behavior because they actively help when there are activities in the community. This study aims to describe the two sides of the life of adolescent slot gambling players in Telaga Silaba Village in their social life. This research uses a type of qualitative research with a descriptive approach. The results showed negative behavior of Bubuhan Cucu Kai in the form they like to play slot gambling, use spending money given by their parents to play slots, then the winning money from playing slot gambling is used to buy alcohol and hang out until morning around 02:00. While the positive behavior of Bubuhan Cucu Kai was in the form of their liking to help with activities in the community such as helping residents' wedding receptions, helping with the funeral process for residents who died and helping with the Isra Mi'raj and Maulid Nabi Muhammad SAW commemorations. This study concludes that the negative behavior of Bubuhan Cucu Kai is based on differences in standard values ​​and norms with the dominant society and there are also social values ​​such as material values, vital values ​​and aesthetic values ​​that underlie this group's negative behavior. Meanwhile, Bubuhan Cucu Kai's positive behavior is based on the existence of several social values ​​that they believe in, such as material values, vital values, religious values ​​and moral values.